PELAKSANAAN RESTORATIVE JUSTISE, DIVERSI DAN ULTIMUM REMIDUM DALAM SISTEM PERADILAN PIDANA ANAK DI INDONESIA - Hamzah, Hasrul; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
The juvenile justice system in Indonesia is still weak, resulting in misuse of the law in enforcing criminal law, especially against children. The justice system provides protection for juveniles who commit offenses. This research aims to examine restorative justice media, diversion and ultimum remedium in the application of criminal justice to juvenile crimes. Descriptive normative legal research is used in this lesson. examine laws relating to the juvenile justice system. This fundamental transformation involves the implementation of restorative justice through a diversion program. The success of diversion is determined by positive subjective will and the fulfillment of conditions. The use of Ultimum Remedium can take into account the interests of criminals. The obstacle to implementing Ultimum remedium, if the act to the interests of the state or the people, then criminal sanctions will be the main pain (primum remedium).Keywords: Restorative Justice, Diversion, Ultimum Remedium, Juvenile Criminal Justice System